Kajian finansial alat keselamatan pada kapal nelayan pole and line di Kota Baubau - Afandu, Aswad; Lawelle, Sjamsu Alam; Nurdiana A; Afyudi, Bobby; Kamri, Syamsul (Universitas Halu Oleo, 2024)
This study is Financial Study of Safety Equipment on Pole and Line (Huhate) Ships in Baubau City. The aim of this study was to determine the type and number of safety equipment, the price of safety equipment and the proportion of the cost of safety equipment from the price of ships in Baubau City. This research was carried out January 2024.The sampling used in research uses descriptive qualitative methods. The sampling used in this study was the Purposive Sampling. Research data was obtained through surveys, observations, interviews and documentation. Data analysis used was descriptive analysis and percentages. The results showed that the types of safety equipment available on Pole and Line ships in Baubau City were life jacket, life buoy, compass, APAR (Fire extinguisher), radio, first aid kit, echosounder, jerry cans, tires, inner tires and back pack. The average proportion of the cost of safety equipment from the price of the ship 10 GT ship with an average price of safety equipment was IDR 4,913,200 from an average ship price of IDR 168,000,000 with a percentage of 2.95% and for a 15 GT ship with an average price of safety equipment was IDR 6,186,400 from the average ship price IDR 161,000,000 with a percentage of 3.90%.This results of this research conclude that there is still a lack of awareness among fishermen in equipping safety equipment on boats.